STAT4 isoforms differentially regulate Th1 cytokine production and the severity of inflammatory bowel disease - O’Malley, John T. (2008)
STAT4, a critical regulator of inflammation in vivo, can be expressed as two alternative splice forms, a full-length STAT4α, and a STAT4β isoform lacking a C-terminal transactivation domain. Each isoform is sufficient to program Th1 development through both common and distinct subsets of target genes. However, the ability of these isoforms to mediate inflammation in vivo has not been examined. Using a model of colitis that develops following transfer of CD4+ CD45RB(hi) T-cells expressing either the STAT4α or STAT4β isoform into SCID mice, we determined that while both isoforms mediate inflammation and weight loss, STAT4β promotes greater colonic inflammation and tissue destruction. This correlates with STAT4 isoform-dependent expression of TNF-α and GM-CSF in vitro and in vivo, but not Th1 expression of IFN-γ or Th17 expression of IL-17, which were similar in STAT4α- and STAT4β-expressing T cells. Thus, higher expression of a subset of inflammatory cytokines from STAT4β-expressing T cells correlates with the ability of STAT4β-expressing T cells to mediate more severe inflammatory disease.